2010
DOI: 10.1002/pi.2922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Sm(III)–hyperbranched poly(ester‐amide) complex

Abstract: A novel Sm(III)–hyperbranched poly(ester‐amide) complex (Sm(III)–HBPEA) was synthesized, and characterized using Fourier transform infrared, 13C NMR and fluorescence spectroscopy and thermogravimetric analysis. Under the conditions used, HBPEA chelates to Sm3+ ions mainly via oxygen and nitrogen atoms of functional groups on the HBPEA chain. Modes of bonding of carboxyl groups, terminal hydroxyl groups and amide carbonyl structures may play the most important role in the coordination interaction. On excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Particularly, we have observed that the carbon signal of the carboxylic acid in the 13 C CP-MAS spectra (cross-polarization and magic angle spinning) is a sensitive parameter to sense the union of Cu(II) to this ligand (RCO 2 H) [34]. Chen et al have also observed similar changes in the 13 C NMR spectra in solution for Sm(III)-hyperbranched poly(ester-amide) [35].…”
Section: Introductionmentioning
confidence: 52%
“…Particularly, we have observed that the carbon signal of the carboxylic acid in the 13 C CP-MAS spectra (cross-polarization and magic angle spinning) is a sensitive parameter to sense the union of Cu(II) to this ligand (RCO 2 H) [34]. Chen et al have also observed similar changes in the 13 C NMR spectra in solution for Sm(III)-hyperbranched poly(ester-amide) [35].…”
Section: Introductionmentioning
confidence: 52%
“…On the other hand, the ss -NMR technique retrieves information on the ligands involved in the coordination of paramagnetic ions due to the enhancement in the relaxation behavior of different nuclei present in the polymer matrix ( 1 H, 13 C, 15 N, etc.). In particular, we have previously demonstrated that 13 C CP-MAS experiments are effective for studying the preferences in the uptake of copper­(II) ions at different concentrations of metal ions in polyelectrolyte and polyampholyte materials; however, some experimental conditions must be taken into account prior to setting the acquisition parameters, such as the contact time used in the cross-polarization steps in the CP-MAS experiments. ,, Also, some other authors have used this strategy to study the coordination of mercury, samarium, and zinc in polymer matrixes. In this work, the 13 C CP-MAS spectra were used to characterize the environment of the Co­(II) ions after the uptake of the paramagnetic ions depending the different functional groups present in polymer materials.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the direct polarization or cross-polarization strategies commonly employed in the acquisition of 13 C ss-NMR experiments for structural purposes can detect which segments/regions of the polymeric material are close to the paramagnetic entities. With this aim, different authors have been used NMR as an approach to find out which ligands present in polymeric networks are involved in the coordination of Cu [23,24], Hg [25], Co [23,26], and Sm [27] ions in non-crystalline systems.…”
Section: Resultsmentioning
confidence: 99%